A kind of PPS engineering plastic and preparation method thereof
Through the modification of glass fiber, the problem of poor bonding of polyphenylene sulfide and glass fiber is solved, the toughness and processing performance of PPS engineering plastics are improved, and excellent impact and bending strength and stable mechanical properties are achieved.
Patent Information
- Application Number
- CN202310237165.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-13
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-03-13
AI Technical Summary
Polyphenylene sulfide engineering plastics have problems such as poor interfacial bonding and poor compatibility when reinforcing with glass fiber, resulting in poor processing performance and unstable performance.
By modifying the glass fibers, pretreated in the hydroxylated solution to increase the active groups, then silane treatment is performed using silane combination reagents such as p-aminophenyltrimethoxysilane and styrene ethyltrimethoxysilane. Then, water-based polyurethane and polyimide are used to further modify the modified graphene to form a dense protective layer and good bonding, improving interface compatibility and mechanical properties.
It significantly improves the toughness and processing properties of PPS engineering plastics, enhances impact strength and bending strength, ensures the stability and heat resistance of mechanical properties, and avoids performance degradation caused by interface slip.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of plastics, and in particular relates to a PPS engineering plastic and a preparation method thereof. Background Art
[0002] Polyphenylene sulfide (PPS) is a high molecular polymer containing phenylthio groups on the main chain of the molecule. It is a crystalline polymer with great rigidity and regularity in its molecular chain. As one of the six major engineering plastics along with polyester, polyoxymethylene, polyphenylene ether, polycarbonate and nylon, polyphenylene sulfide has excellent chemical resistance, electrical insulation, tensile properties and flame retardancy. It can reach the UL94-V0 level without adding flame retardants and is widely used in automotive parts, mechanical parts, electronic and electrical parts and other fields. Polyphenylene sulfide also has disadvantages such as poor toughness and poor processing and forming properties. At present, polyphenylene sulfide is mainly modified by adding some dispersed reinforcing fibers and inorganic fillers. However, inorganic particles have poor dispersibility in the resin matrix and weak ability to modify specific functions.
[0003] Chinese patent CN105802225A discloses a modified polyphenylene sulfide reinforced plastic, including the following raw materials: polyphenylene sulfide, glass fiber, carbon fiber, aramid fiber, polytetrafluoroethylene, and polytetrafluoroethylene. The patent enhances the mechanical properties, self-lubricating properties, and flame retardant properties of polyphenylene sulfide by adding fillers such as glass fiber to the blend. However, the direct addition of inorganic components such as glass fiber and carbon fiber has poor compatibility with organic resins, and the modification ability is limited. Summary of the invention
[0004] In view of the above-mentioned defects of the prior art, the present invention provides a PPS engineering plastic and a preparation method thereof. The PPS engineering plastic improves the toughness of the PPS resin by adding modified glass fiber and a compatibilizer, so that the PPS engineering plastic has excellent mechanical properties and processing properties.
[0005] A PPS engineering plastic comprises the following raw materials: 80-90 parts by weight of PPS resin, 30-40 parts by weight of modified glass fiber, 1-3 parts by weight of compatibilizer, 0.2-0.5 parts by weight of antioxidant, 0.2-0.5 parts by weight of lubricant and 0.2-0.5 parts by weight of auxiliary agent.
[0006] Glass fiber can improve the thermal stability, impact resistance, low warpage, etc. of engineering plastics as a reinforcing filler. However, glass fiber itself is a highly polar inorganic material, which mainly includes components such as silicon oxide, aluminum oxide, calcium oxide, boron oxide, and magnesium oxide, and has the problems of poor interface bonding and poor compatibility with the organic polymer PPS resin. This makes the glass fiber not only have poor processing performance (PPS will produce hair scraps, debris, etc. during processing) when used as a reinforcing material, but also affect the stress transfer between the glass fiber and the PPS resin, which has an adverse effect on the performance of engineering plastics. For this reason, the present invention modifies the glass fiber.
[0007] The preparation method of the modified glass fiber is:
[0008] A1, adding glass fiber to a hydroxylation solution to react, thereby obtaining pretreated glass fiber;
[0009] A2. Add p-aminophenyltrimethoxysilane and styreneethyltrimethoxysilane into DMF, and then add pretreated glass fiber to react to obtain modified glass fiber.
[0010] The present invention first pre-treats the glass fiber by a hydroxylation solution to increase the active groups on the surface of the glass fiber. Then, the pre-treated glass fiber is silane-treated by a silane combination reagent, and styrene ethyl trimethoxy silane and p-aminophenyl trimethoxy silane are used as silane combination reagents to improve bonding ability. It has excellent temperature resistance and a structure similar to the phenyl segment of the PPS resin, which plays a bridge role between the PPS resin and the glass fiber, and gives the glass fiber surface good compatibility with the matrix resin. In addition, silane treatment of the glass fiber is also conducive to the subsequent imide ring and polyurethane to be more closely combined with the glass fiber, while helping the glass fiber to be combined with the resin, effectively preventing the problem of plastic performance degradation caused by slippage due to external damage to the interface.
[0011] Preferably, the preparation method of the modified glass fiber is:
[0012] A1, adding glass fiber to a hydroxylation solution to react, thereby obtaining pretreated glass fiber;
[0013] A2, adding p-aminophenyltrimethoxysilane and styreneethyltrimethoxysilane to DMF, and then adding pretreated glass fiber to react to obtain silane-treated glass fiber;
[0014] A3. Add waterborne polyurethane and polyimide into water and homogenize, then add modified graphene and silane treated glass fiber to react to obtain modified glass fiber.
[0015] Furthermore, the present invention modifies glass fiber by waterborne polyurethane, polyimide and modified graphene. The waterborne polyurethane has a large molecular weight and contains strong polar groups. It can form a dense protective layer on the surface of the glass fiber to isolate the outside world and repair the microcracks on the surface of the glass fiber, which is conducive to ensuring the stability of mechanical properties. At the same time, the active amino groups contained in it can effectively protect the glass fiber during high-temperature processing and form a good combination with the resin. Polyimide has good heat resistance, and its main structure is that the imide can form a good combination with the phenylthio group in the PPS resin, which is a good auxiliary polyurethane to improve the heat resistance of the system, and avoid the aggregation of polyurethane during high-temperature processing, which has an adverse effect on the combination of glass fiber and resin. The surface tension of the modified graphene is small, not easy to agglomerate, and the surface contains carboxyl groups, which are evenly distributed in the homogenous liquid. After grafting with the glass fiber, it can play its own mechanical advantages well, improve the reinforcing effect of the glass fiber, and make the performance of engineering plastics more excellent and stable.
[0016] Preferably, the preparation method of the modified glass fiber is:
[0017] A1. Add 10-15 parts by weight of glass fiber to 40-60 parts by weight of hydroxylation solution and mix evenly. Reflux for reaction at 105-115° C. for 2-3 hours. After reaction, filter and dry to obtain pretreated glass fiber.
[0018] A2, adding 3-5 parts by weight of p-aminophenyltrimethoxysilane and 1-2 parts by weight of styreneethyltrimethoxysilane to 20-40 parts by weight of DMF and mixing evenly, then adding 7-10 parts by weight of pretreated glass fiber, reacting at 70-75° C. for 10-15 hours, filtering and drying after completion, to obtain silane-treated glass fiber;
[0019] A3. Add 2-5 parts by weight of aqueous polyurethane and 1-3 parts by weight of polyimide to 90-100 parts by weight of water, mix evenly, and homogenize for 2-5 minutes. Then add 0.5-1.5 parts by weight of modified graphene and 4-6 parts by weight of silane-treated glass fiber, react at 40-50° C. for 1-3 hours, filter and dry after reaction to obtain modified glass fiber.
[0020] Preferably, the hydroxylation solution is composed of 20-30wt% hydrogen peroxide and 92-98wt% sulfuric acid in a mass ratio of 5-7:1.
[0021] Preferably, the homogenization condition is 7000-10000r / min.
[0022] Preferably, the preparation method of the modified graphene is:
[0023] 0.5-0.7 parts by weight of graphene oxide are added to 120-160 parts by weight of water, mixed evenly, and ultrasonicated for 0.5-2 hours; then 0.6-1 parts by weight of hydrazine are added, and the mixture is reacted at 90-95° C. for 18-22 hours; after cooling to 65-70° C., 0.7-1 parts by weight of 3-aminobiphenyl-3-carboxylic acid, 8-12 parts by weight of an ethanol solution of tert-butyl nitrite and 0.2-0.4 parts by weight of potassium hydroxide are added, and the mixture is reacted for 18-22 hours; after the mixture is reacted, the pH is adjusted to neutral, filtered and dried to obtain modified graphene.
[0024] Preferably, the ultrasonic conditions are: ultrasonic power 400-600W, ultrasonic frequency 20-35kHz.
[0025] Preferably, the concentration of the ethanol solution of tert-butyl nitrite is 0.1-0.3 wt %.
[0026] The compatibilizer is at least one of glycidyl methacrylate grafted ethylene-octene copolymer, ethylene-butyl acrylate-glycidyl methacrylate copolymer, ethylene glycidyl methacrylate-vinyl alcohol copolymer, and methyl acrylate and glycidyl methacrylate terpolymer.
[0027] The present invention preferably uses ethylene-butyl acrylate-glycidyl methacrylate copolymer and glycidyl methacrylate grafted ethylene-octene copolymer to form a compatibilizer, wherein the epoxy group contained therein can react with the sulfhydryl group of the PPS resin and the hydroxyl group on the surface of the modified glass fiber, effectively improving the interface bonding and compatibility between the PPS resin and the glass fiber. In addition, the inventors have also found that the above-mentioned compatibilizer combination also has a certain contribution to improving the toughness of PPS engineering plastics.
[0028] Preferably, the compatibilizer is a mixture of ethylene-butyl acrylate-glycidyl methacrylate copolymer and glycidyl methacrylate grafted ethylene-octene copolymer; the mass ratio of the ethylene-butyl acrylate-glycidyl methacrylate copolymer to the glycidyl methacrylate grafted ethylene-octene copolymer is 1-2:1.
[0029] The antioxidant is at least one of triphenyl phosphite, 3,3'-dioctadecyl thiodipropionate, 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 1,1,3-tri(5-tert-butyl-4-hydroxy-2-methylphenyl)butane.
[0030] Preferably, the antioxidant is a mixture of triphenyl phosphite and 3-(3,5-di-tert-butyl-4-hydroxyphenyl)octadecyl propionate; the mass ratio of triphenyl phosphite to 3-(3,5-di-tert-butyl-4-hydroxyphenyl)octadecyl propionate is 1-3:1.
[0031] The lubricant is at least one of pentaerythritol stearate, stearic acid amide, polyethylene wax and silicone powder.
[0032] Preferably, the lubricant is pentaerythritol stearate.
[0033] The auxiliary agent is any one of zinc oxide, titanium dioxide and zirconium oxide.
[0034] Preferably, the auxiliary agent is zinc oxide.
[0035] The invention also provides a method for preparing the PPS engineering plastic.
[0036] The preparation method of the above-mentioned PPS engineering plastics comprises the following steps:
[0037] PPS resin, compatibilizer, antioxidant, lubricant and auxiliary agent are mixed by weight and added from the main feeding port of a twin-screw extruder, and modified glass fiber is added from the side feeding port of the twin-screw extruder, melted, extruded and granulated to obtain the PPS engineering plastic.
[0038] Beneficial effects of the present invention:
[0039] The PPS engineering plastic provided by the present invention has good toughness and processability, and is excellent in impact strength and bending strength. The modified glass fiber used in the present invention can avoid the problems of poor interface bonding with PPS resin, poor compatibility, and poor processing performance when glass fiber is directly added as a reinforcing material. The present invention increases the active groups on the surface of the glass fiber through a hydroxylation solution, and then uses styrene ethyl trimethoxy silane and p-aminophenyl trimethoxy silane as a silane combination reagent to improve the bonding ability, which plays a bridge role between the PPS resin and the glass fiber, and gives the glass fiber surface good compatibility with the matrix resin. Finally, the glass fiber is modified by waterborne polyurethane, polyimide and modified graphene. The waterborne polyurethane can form a dense protective layer on the surface of the glass fiber to isolate it from the outside world and repair the microcracks on the surface of the glass fiber, which is beneficial to ensure the stability of the mechanical properties. The polyimide has good heat resistance, and its main structure is imide, which can form a good combination with the phenylthio group in the PPS resin, and can assist the polyurethane to improve the heat resistance of the system and avoid the aggregation of polyurethane during high-temperature processing, which has an adverse effect on the combination of glass fiber and resin. The surface tension of the modified graphene is small and it is not easy to agglomerate. It also contains carboxyl groups on the surface. After grafting with the glass fiber, it can give full play to its own mechanical advantages, improve the reinforcement effect of the glass fiber, and make the performance of engineering plastics more excellent and stable. DETAILED DESCRIPTION
[0040] The above content of the present invention is further described in detail below in conjunction with specific implementation modes, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments.
[0041] PPS resin, brand: LTP CE-2212, was purchased from Chengdu Lotte Plastics Co., Ltd.
[0042] Glass fiber, short-cut fiber, length: 3-4.5 mm, alkali-free, purchased from Taian Songze Composite Materials Co., Ltd.
[0043] Glycidyl methacrylate grafted ethylene-octene copolymer, POE-g-GMA, model: SOG-03 was purchased from Jiayirong Polymer (Shanghai) Co., Ltd.
[0044] Ethylene-butyl acrylate-glycidyl methacrylate copolymer, EMA-g-GMA, model: PTW was purchased from Ningbo Yashi Tongchuang Chemical Technology Co., Ltd.
[0045] Maleic anhydride grafted styrene-ethylene-butadiene-styrene copolymer, SEBS-G-MAH, model: FG1901 was purchased from Dongguan Shenghao Plastic Raw Materials Co., Ltd.
[0046] Graphene oxide, model: HWG24600, thickness: 0.8-1.2 nm, single layer, purchased from Beijing Huawei Ruike Chemical Co., Ltd.
[0047] Polyimide, solid content: 18%, viscosity: 15-18 Pa.s, purchased from Changzhou Runchuan Plastic Material Co., Ltd.
[0048] Waterborne polyurethane, model: RL-8401, content: 53%, viscosity: 247 mPa.s, purchased from Guangzhou Ruilin New Materials Co., Ltd.
[0049] Example 1
[0050] A PPS engineering plastic is prepared from the following raw materials: 85 parts by weight of PPS resin, 35 parts by weight of modified glass fiber, 2.2 parts by weight of a compatibilizer, 0.4 parts by weight of an antioxidant, 0.3 parts by weight of a lubricant, and 0.3 parts by weight of an auxiliary agent.
[0051] The compatibilizer is a mixture of ethylene-butyl acrylate-glycidyl methacrylate copolymer and glycidyl methacrylate grafted ethylene-octene copolymer in a mass ratio of 1.5:1.
[0052] The antioxidant is a mixture of triphenyl phosphite and 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate in a mass ratio of 2:1.
[0053] The lubricant is pentaerythritol stearate.
[0054] The auxiliary agent is zinc oxide.
[0055] The preparation method of the modified glass fiber is:
[0056] A1. Add 12 parts by weight of glass fiber to 50 parts by weight of hydroxylation solution, mix well, and reflux at 110° C. for 2.5 hours. After completion, filter and dry to obtain pretreated glass fiber; the hydroxylation solution is composed of 25wt% hydrogen peroxide and 95wt% sulfuric acid in a mass ratio of 6:1;
[0057] A2, adding 3.5 parts by weight of p-aminophenyltrimethoxysilane and 1.5 parts by weight of styreneethyltrimethoxysilane to 30 parts by weight of DMF and mixing evenly, then adding 8 parts by weight of pretreated glass fiber, reacting at 72° C. for 12 hours, filtering and drying after the reaction, to obtain silane-treated glass fiber;
[0058] A3. Add 3 parts by weight of aqueous polyurethane and 2 parts by weight of polyimide to 95 parts by weight of water and mix evenly. Homogenize at 8000 r / min for 3 min. Then add 1 part by weight of modified graphene and 5 parts by weight of silane-treated glass fiber. React at 45° C. for 2 h. After reaction, filter and dry to obtain modified glass fiber.
[0059] The preparation method of the modified graphene is:
[0060] 0.6 parts by weight of graphene oxide was added to 150 parts by weight of water and mixed evenly, and ultrasonicated at 500 W and 30 kHz for 1 hour; then 0.8 parts by weight of hydrazine was added, and the mixture was reacted at 92° C. for 20 hours; after cooling to 68° C., 0.8 parts by weight of 3-aminobiphenyl-3-carboxylic acid, 10 parts by weight of 0.2wt% ethanol solution of tert-butyl nitrite and 0.3 parts by weight of potassium hydroxide were added, and the reaction was continued for 20 hours; after the reaction was completed, the pH was adjusted to neutral, filtered and dried to obtain modified graphene.
[0061] A method for preparing PPS engineering plastics comprises the following steps:
[0062] PPS resin, compatibilizer, antioxidant, lubricant and auxiliary agent are mixed by weight and added from the main feeding port of the twin-screw extruder, and modified glass fiber is added from the side feeding port of the twin-screw extruder, melted, extruded and granulated to obtain the PPS engineering plastic. Among them, the die temperature is 305°C, the screw speed is 550r / min, the temperature of zone 1 is 300°C, the temperature of zone 2 is 305°C, the temperature of zone 3 is 305°C, the temperature of zone 4 is 310°C, the temperature of zone 5 is 310°C, the temperature of zone 6 is 305°C, the temperature of zone 7 is 305°C, and the temperature of zone 8 is 305°C.
[0063] Example 2
[0064] A PPS engineering plastic is prepared from the following raw materials: 85 parts by weight of PPS resin, 35 parts by weight of modified glass fiber, 2.2 parts by weight of a compatibilizer, 0.4 parts by weight of an antioxidant, 0.3 parts by weight of a lubricant, and 0.3 parts by weight of an auxiliary agent.
[0065] The compatibilizer is a mixture of ethylene-butyl acrylate-glycidyl methacrylate copolymer and glycidyl methacrylate grafted ethylene-octene copolymer in a mass ratio of 1.5:1.
[0066] The antioxidant is a mixture of triphenyl phosphite and 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate in a mass ratio of 2:1.
[0067] The lubricant is pentaerythritol stearate.
[0068] The auxiliary agent is zinc oxide.
[0069] The preparation method of the modified glass fiber is:
[0070] A1. Add 12 parts by weight of glass fiber to 50 parts by weight of hydroxylation solution, mix well, and reflux at 110° C. for 2.5 hours. After completion, filter and dry to obtain pretreated glass fiber; the hydroxylation solution is composed of 25wt% hydrogen peroxide and 95wt% sulfuric acid in a mass ratio of 6:1;
[0071] A2. Add 3 parts by weight of aqueous polyurethane and 2 parts by weight of polyimide to 95 parts by weight of water and mix evenly. Homogenize at 8000 r / min for 3 min. Then add 1 part by weight of modified graphene and 5 parts by weight of pretreated glass fiber. React at 45° C. for 2 h. After reaction, filter and dry to obtain modified glass fiber.
[0072] The preparation method of the modified graphene is:
[0073] 0.6 parts by weight of graphene oxide was added to 150 parts by weight of water and mixed evenly, and ultrasonicated at 500 W and 30 kHz for 1 hour; then 0.8 parts by weight of hydrazine was added, and the mixture was reacted at 92° C. for 20 hours; after cooling to 68° C., 0.8 parts by weight of 3-aminobiphenyl-3-carboxylic acid, 10 parts by weight of 0.2wt% ethanol solution of tert-butyl nitrite and 0.3 parts by weight of potassium hydroxide were added, and the reaction was continued for 20 hours; after the reaction was completed, the pH was adjusted to neutral, filtered and dried to obtain modified graphene.
[0074] A method for preparing PPS engineering plastics comprises the following steps:
[0075] PPS resin, compatibilizer, antioxidant, lubricant and auxiliary agent are mixed by weight and added from the main feeding port of the twin-screw extruder, and modified glass fiber is added from the side feeding port of the twin-screw extruder, melted, extruded and granulated to obtain the PPS engineering plastic. Among them, the die temperature is 305°C, the screw speed is 550r / min, the temperature of zone 1 is 300°C, the temperature of zone 2 is 305°C, the temperature of zone 3 is 305°C, the temperature of zone 4 is 310°C, the temperature of zone 5 is 310°C, the temperature of zone 6 is 305°C, the temperature of zone 7 is 305°C, and the temperature of zone 8 is 305°C.
[0076] Example 3
[0077] A PPS engineering plastic is prepared from the following raw materials: 85 parts by weight of PPS resin, 35 parts by weight of modified glass fiber, 2.2 parts by weight of a compatibilizer, 0.4 parts by weight of an antioxidant, 0.3 parts by weight of a lubricant, and 0.3 parts by weight of an auxiliary agent.
[0078] The compatibilizer is a mixture of ethylene-butyl acrylate-glycidyl methacrylate copolymer and glycidyl methacrylate grafted ethylene-octene copolymer in a mass ratio of 1.5:1.
[0079] The antioxidant is a mixture of triphenyl phosphite and 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate in a mass ratio of 2:1.
[0080] The lubricant is pentaerythritol stearate.
[0081] The auxiliary agent is zinc oxide.
[0082] The preparation method of the modified glass fiber is:
[0083] A1. Add 12 parts by weight of glass fiber to 50 parts by weight of hydroxylation solution, mix well, and reflux at 110° C. for 2.5 hours. After completion, filter and dry to obtain pretreated glass fiber; the hydroxylation solution is composed of 25wt% hydrogen peroxide and 95wt% sulfuric acid in a mass ratio of 6:1;
[0084] A2. Add 3.5 parts by weight of p-aminophenyltrimethoxysilane and 1.5 parts by weight of styreneethyltrimethoxysilane to 30 parts by weight of DMF and mix well. Then add 8 parts by weight of pretreated glass fiber and react at 72° C. for 12 hours. After reaction, filter and dry to obtain modified glass fiber.
[0085] A method for preparing PPS engineering plastics comprises the following steps:
[0086] PPS resin, compatibilizer, antioxidant, lubricant and auxiliary agent are mixed by weight and added from the main feeding port of the twin-screw extruder, and modified glass fiber is added from the side feeding port of the twin-screw extruder, melted, extruded and granulated to obtain the PPS engineering plastic. Among them, the die temperature is 305°C, the screw speed is 550r / min, the temperature of zone 1 is 300°C, the temperature of zone 2 is 305°C, the temperature of zone 3 is 305°C, the temperature of zone 4 is 310°C, the temperature of zone 5 is 310°C, the temperature of zone 6 is 305°C, the temperature of zone 7 is 305°C, and the temperature of zone 8 is 305°C.
[0087] Example 4
[0088] A PPS engineering plastic is prepared from the following raw materials: 85 parts by weight of PPS resin, 35 parts by weight of modified glass fiber, 2.2 parts by weight of a compatibilizer, 0.4 parts by weight of an antioxidant, 0.3 parts by weight of a lubricant, and 0.3 parts by weight of an auxiliary agent.
[0089] The compatibilizer is a mixture of ethylene-butyl acrylate-glycidyl methacrylate copolymer and glycidyl methacrylate grafted ethylene-octene copolymer in a mass ratio of 1.5:1.
[0090] The antioxidant is a mixture of triphenyl phosphite and 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate in a mass ratio of 2:1.
[0091] The lubricant is pentaerythritol stearate.
[0092] The auxiliary agent is zinc oxide.
[0093] The preparation method of the modified glass fiber is:
[0094] A1. Add 12 parts by weight of glass fiber to 50 parts by weight of hydroxylation solution, mix well, and reflux at 110° C. for 2.5 hours. After completion, filter and dry to obtain pretreated glass fiber; the hydroxylation solution is composed of 25wt% hydrogen peroxide and 95wt% sulfuric acid in a mass ratio of 6:1;
[0095] A2, adding 3.5 parts by weight of p-aminophenyltrimethoxysilane and 1.5 parts by weight of styreneethyltrimethoxysilane to 30 parts by weight of DMF and mixing evenly, then adding 8 parts by weight of pretreated glass fiber, reacting at 72° C. for 12 hours, filtering and drying after the reaction, to obtain silane-treated glass fiber;
[0096] A3. Add 3 parts by weight of aqueous polyurethane and 2 parts by weight of polyimide to 95 parts by weight of water and mix evenly. Homogenize at 8000 r / min for 3 min. Then add 1 part by weight of graphene oxide and 5 parts by weight of silane-treated glass fiber. React at 45° C. for 2 h. After reaction, filter and dry to obtain modified glass fiber.
[0097] A method for preparing PPS engineering plastics comprises the following steps:
[0098] PPS resin, compatibilizer, antioxidant, lubricant and auxiliary agent are mixed by weight and added from the main feeding port of the twin-screw extruder, and modified glass fiber is added from the side feeding port of the twin-screw extruder, melted, extruded and granulated to obtain the PPS engineering plastic. Among them, the die temperature is 305°C, the screw speed is 550r / min, the temperature of zone 1 is 300°C, the temperature of zone 2 is 305°C, the temperature of zone 3 is 305°C, the temperature of zone 4 is 310°C, the temperature of zone 5 is 310°C, the temperature of zone 6 is 305°C, the temperature of zone 7 is 305°C, and the temperature of zone 8 is 305°C.
[0099] Example 5
[0100] A PPS engineering plastic is prepared from the following raw materials: 85 parts by weight of PPS resin, 35 parts by weight of glass fiber, 2.2 parts by weight of a compatibilizer, 0.4 parts by weight of an antioxidant, 0.3 parts by weight of a lubricant, and 0.3 parts by weight of an auxiliary agent.
[0101] The compatibilizer is a mixture of ethylene-butyl acrylate-glycidyl methacrylate copolymer and glycidyl methacrylate grafted ethylene-octene copolymer in a mass ratio of 1.5:1.
[0102] The antioxidant is a mixture of triphenyl phosphite and 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate in a mass ratio of 2:1.
[0103] The lubricant is pentaerythritol stearate.
[0104] The auxiliary agent is zinc oxide.
[0105] A method for preparing PPS engineering plastics comprises the following steps:
[0106] PPS resin, compatibilizer, antioxidant, lubricant and auxiliary agent are mixed by weight and added from the main feeding port of the twin-screw extruder, glass fiber is added from the side feeding port of the twin-screw extruder, melted, extruded and granulated to obtain the PPS engineering plastic. Among them, the die temperature is 305°C, the screw speed is 550r / min, the temperature of zone 1 is 300°C, the temperature of zone 2 is 305°C, the temperature of zone 3 is 305°C, the temperature of zone 4 is 310°C, the temperature of zone 5 is 310°C, the temperature of zone 6 is 305°C, the temperature of zone 7 is 305°C, and the temperature of zone 8 is 305°C.
[0107] Example 6
[0108] A PPS engineering plastic is prepared from the following raw materials: 85 parts by weight of PPS resin, 35 parts by weight of modified glass fiber, 2.2 parts by weight of a compatibilizer, 0.4 parts by weight of an antioxidant, 0.3 parts by weight of a lubricant, and 0.3 parts by weight of an auxiliary agent.
[0109] The compatibilizer is maleic anhydride grafted styrene-ethylene-butadiene-styrene copolymer.
[0110] The antioxidant is a mixture of triphenyl phosphite and 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate in a mass ratio of 2:1.
[0111] The lubricant is pentaerythritol stearate.
[0112] The auxiliary agent is zinc oxide.
[0113] The preparation method of the modified glass fiber is:
[0114] A1. Add 12 parts by weight of glass fiber to 50 parts by weight of hydroxylation solution, mix well, and reflux at 110° C. for 2.5 hours. After completion, filter and dry to obtain pretreated glass fiber; the hydroxylation solution is composed of 25wt% hydrogen peroxide and 95wt% sulfuric acid in a mass ratio of 6:1;
[0115] A2, adding 3.5 parts by weight of p-aminophenyltrimethoxysilane and 1.5 parts by weight of styreneethyltrimethoxysilane to 30 parts by weight of DMF and mixing evenly, then adding 8 parts by weight of pretreated glass fiber, reacting at 72° C. for 12 hours, filtering and drying after the reaction, to obtain silane-treated glass fiber;
[0116] A3. Add 3 parts by weight of aqueous polyurethane and 2 parts by weight of polyimide to 95 parts by weight of water and mix evenly. Homogenize at 8000 r / min for 3 min. Then add 1 part by weight of modified graphene and 5 parts by weight of silane-treated glass fiber. React at 45° C. for 2 h. After reaction, filter and dry to obtain modified glass fiber.
[0117] The preparation method of the modified graphene is:
[0118] 0.6 parts by weight of graphene oxide was added to 150 parts by weight of water and mixed evenly, and ultrasonicated at 500 W and 30 kHz for 1 hour; then 0.8 parts by weight of hydrazine was added, and the mixture was reacted at 92° C. for 20 hours; after cooling to 68° C., 0.8 parts by weight of 3-aminobiphenyl-3-carboxylic acid, 10 parts by weight of 0.2wt% ethanol solution of tert-butyl nitrite and 0.3 parts by weight of potassium hydroxide were added, and the reaction was continued for 20 hours; after the reaction was completed, the pH was adjusted to neutral, filtered and dried to obtain modified graphene.
[0119] A method for preparing PPS engineering plastics comprises the following steps:
[0120] PPS resin, compatibilizer, antioxidant, lubricant and auxiliary agent are mixed by weight and added from the main feeding port of the twin-screw extruder, and modified glass fiber is added from the side feeding port of the twin-screw extruder, melted, extruded and granulated to obtain the PPS engineering plastic. Among them, the die temperature is 305°C, the screw speed is 550r / min, the temperature of zone 1 is 300°C, the temperature of zone 2 is 305°C, the temperature of zone 3 is 305°C, the temperature of zone 4 is 310°C, the temperature of zone 5 is 310°C, the temperature of zone 6 is 305°C, the temperature of zone 7 is 305°C, and the temperature of zone 8 is 305°C.
[0121] Test Example 1
[0122] Bending performance test: The PPS engineering plastics of the above embodiment were injected into a sample by an injection molding machine, and the bending performance test was performed according to GB / T9341-2008 "Determination of Bending Performance of Plastics". The thickness of the sample was 4 mm, and 10 groups of each embodiment were tested in parallel to take the average value.
[0123] Table 1. Bending properties of PPS engineering plastics
[0124] Bending strength, MPa Example 1 165.0 Example 2 156.7 Example 3 154.2 Example 4 160.1 Example 5 146.3 Example 6 162.8
[0125] Test Example 2
[0126] Impact performance test: The PPS engineering plastics of the above embodiment were injection molded by an injection molding machine to prepare samples, and the impact performance test was performed according to GB / T1043.1-2008 "Determination of impact properties of simply supported beams of plastics Part 1: Non-instrumented impact test". The thickness of the sample was 4 mm, and 10 groups of each embodiment were tested in parallel to take the average value.
[0127] Table 2. Impact properties of PPS engineering plastics
[0128] <![CDATA[Notched impact strength of simply supported beam, kJ / m 2 > Example 1 21.9 Example 2 18.3 Example 3 16.6 Example 4 19.0 Example 5 12.1 Example 6 20.2
[0129] From the above test results, it can be seen that the PPS engineering plastics of Example 1 have the best impact strength and bending strength. This is because, compared with Examples 2-5, Example 1 increases the active groups on the surface of the glass fiber by hydroxylation solution, and then uses styrene ethyl trimethoxy silane and p-aminophenyl trimethoxy silane as silane combination reagents to improve bonding ability. It has excellent temperature resistance and a structure similar to the phenyl segment of the PPS resin, which plays a bridge role between the PPS resin and the glass fiber, giving the glass fiber surface and the matrix resin good compatibility. In addition, silane treatment of glass fiber is also conducive to the subsequent imide ring and polyurethane to be more closely combined with glass fiber. While helping the glass fiber to combine with the resin, it effectively prevents the problem of plastic performance degradation caused by slippage due to external damage to the interface. Finally, the glass fiber is modified by waterborne polyurethane, polyimide and modified graphene. The waterborne polyurethane can form a dense protective layer on the surface of the glass fiber to isolate it from the outside world and repair the microcracks on the surface of the glass fiber, which is beneficial to ensure the stability of the mechanical properties. The polyimide has good heat resistance, and its main structure is imide, which can form a good combination with the phenylthio group in the PPS resin, and can assist the polyurethane to improve the heat resistance of the system and avoid the aggregation of polyurethane during high-temperature processing, which has an adverse effect on the combination of glass fiber and resin. The surface tension of the modified graphene is small and it is not easy to agglomerate. It also contains carboxyl groups on the surface. After grafting with the glass fiber, it can give full play to its own mechanical advantages, improve the reinforcement effect of the glass fiber, and make the performance of engineering plastics more excellent and stable. Compared with Example 6, Example 1 of the present invention uses ethylene-butyl acrylate-glycidyl methacrylate copolymer and glycidyl methacrylate grafted ethylene-octene copolymer to form a compatibilizer. The epoxy group contained in it can react with the sulfhydryl group of the PPS resin and the hydroxyl group on the surface of the modified glass fiber, which is also beneficial to improve the interface bonding and compatibility between the PPS resin and the glass fiber, and also makes a certain contribution to improving the toughness of the PPS engineering plastic.
[0130] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A PPS engineering plastic, characterized in that: The invention comprises the following raw materials: 80-90 parts by weight of PPS resin, 30-40 parts by weight of modified glass fiber, 1-3 parts by weight of compatibilizer, 0.2-0.5 parts by weight of antioxidant, 0.2-0.5 parts by weight of lubricant, and 0.2-0.5 parts by weight of auxiliary agent; The preparation method of the modified glass fiber is: A1. Add 10-15 parts by weight of glass fiber to 40-60 parts by weight of hydroxylation solution and mix evenly, reflux at 105-115° C. for 2-3 hours, filter and dry after completion to obtain pretreated glass fiber; A2, adding 3-5 parts by weight of p-aminophenyltrimethoxysilane and 1-2 parts by weight of styreneethyltrimethoxysilane to 20-40 parts by weight of DMF and mixing evenly, then adding 7-10 parts by weight of pretreated glass fiber, reacting at 70-75° C. for 10-15 hours, filtering and drying after completion, to obtain silane-treated glass fiber; A3, adding 2-5 parts by weight of aqueous polyurethane and 1-3 parts by weight of polyimide to 90-100 parts by weight of water, mixing evenly, homogenizing for 2-5 minutes, then adding 0.5-1.5 parts by weight of modified graphene and 4-6 parts by weight of silane-treated glass fiber, reacting at 40-50° C. for 1-3 hours, filtering and drying after completion to obtain modified glass fiber; The hydroxylation solution is composed of 20-30wt% hydrogen peroxide and 92-98wt% sulfuric acid in a mass ratio of 5-7:1; The homogenization condition is 7000-10000r / min; The preparation method of the modified graphene is: 0.5-0.7 parts by weight of graphene oxide is added to 120-160 parts by weight of water, mixed evenly, and ultrasonicated for 0.5-2 hours; then 0.6-1 parts by weight of hydrazine is added, and the mixture is reacted at 90-95° C. for 18-22 hours; after cooling to 65-70° C., 0.7-1 parts by weight of 3-aminobiphenyl-3-carboxylic acid, 8-12 parts by weight of ethanol solution of tert-butyl nitrite and 0.2-0.4 parts by weight of potassium hydroxide are added, and the mixture is reacted for 18-22 hours; after the mixture is reacted, the pH is adjusted to neutral, filtered, and dried to obtain modified graphene: wherein the CAS number of 3-aminobiphenyl-3-carboxylic acid is 124221-71-2; The ultrasonic conditions are: ultrasonic power 400-600W, ultrasonic frequency 20-35kHz: The concentration of the ethanol solution of tert-butyl nitrite is 0.1-0.3wt%; The compatibilizer is a mixture of ethylene-butyl acrylate-glycidyl methacrylate copolymer and glycidyl methacrylate grafted ethylene-octene copolymer.
2. The PPS engineering plastic according to claim 1, characterized in that: The antioxidant is at least one of triphenyl phosphite, 3,3'-dioctadecyl thiodipropionate, 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 1,1,3-tri(5-tert-butyl-4-hydroxy-2-methylphenyl)butane.
3. The PPS engineering plastic according to claim 1, characterized in that: The lubricant is at least one of pentaerythritol stearate, stearic acid amide, polyethylene wax and silicone powder.
4. The PPS engineering plastic according to claim 1, characterized in that: The auxiliary agent is any one of zinc oxide, titanium dioxide and zirconium oxide.
5. The method for preparing PPS engineering plastics according to any one of claims 1 to 4, characterized in that: The following steps are involved: PPS resin, compatibilizer, antioxidant, lubricant and auxiliary agent are mixed by weight and added from the main feeding port of a twin-screw extruder, and modified glass fiber is added from the side feeding port of the twin-screw extruder, melted, extruded and granulated to obtain the PPS engineering plastic.
Citation Information
Patent Citations
Modified polyphenylene sulfide enhanced plastic
CN105802225A
Preparation method of polyphenylene sulfide modified composite aggregate
CN102634209A
Graphene oxide-enhanced polyphenylene sulfide composite material and preparation method thereof
CN109320961A
High-toughness wear-resistant polyphenylene sulfide composite material
CN110643179A
Polyphenylene sulfide composite material and preparation method thereof
CN113025039A